2015
DOI: 10.1016/j.gecco.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

A subtropical embayment serves as essential habitat for sub-adults and adults of the critically endangered smalltooth sawfish

Abstract: 2016-11-02T18:49:00

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 27 publications
3
28
1
Order By: Relevance
“…Tagged adults spent the majority of their time at shallow depths (<10 m) and warm water temperatures (22−28°C). In a similar study, Papastamatiou et al (2015) reported that adults rarely occurred in waters warmer than 30°C, although they have occasionally been documented in water 32−34°C (Carlson et al 2014). These data suggest that temperature is a cue for triggering seasonal movements of large juveniles and adults.…”
Section: Large Juveniles and Adultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Tagged adults spent the majority of their time at shallow depths (<10 m) and warm water temperatures (22−28°C). In a similar study, Papastamatiou et al (2015) reported that adults rarely occurred in waters warmer than 30°C, although they have occasionally been documented in water 32−34°C (Carlson et al 2014). These data suggest that temperature is a cue for triggering seasonal movements of large juveniles and adults.…”
Section: Large Juveniles and Adultsmentioning
confidence: 72%
“…Encounter data suggest that larger individuals migrate seasonally northward up the US east coast (NMFS 2009a), although early satellite tracking data were not able to confirm such behavior (Carlson et al 2014). Papastamatiou et al (2015) obtained some evidence to support the migration hypothesis, as northward summer movements were observed from 3 individuals, but no data were collected during late fall and winter to observe subsequent southerly movements. The recapture of an adult in 2015 off Cumberland Island, Georgia, which was originally tagged in 2010 in the Florida Keys (NMFS unpubl.…”
Section: Spatial Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand seasonality of habitat use for migratory fish of conservation concern, grid sampling may help maximize information gained about the animal (e.g. Papastamatiou et al, 2015). Furthermore, grid sampling provides a more rigorous foundation to evaluate the interconnectedness of receiver locations through application of network analysis (Jacoby, Brooks, Croft, & Sims, 2012).…”
Section: Autonomous Receiver Sampling For Survivalmentioning
confidence: 99%
“…Sawfish habitats in the western Atlantic are well documented (e.g. Papastamatiou et al, 2015;Seitz & Poulakis, 2002), and tagging studies have given further insights into sawfish ecology (e.g. Carlson et al, 2014;Guttridge et al, 2015;Simpfendorfer, Wiley, & Yeiser, 2010).…”
mentioning
confidence: 99%